Regional Legislative Oversight of Fiscal Policy in Contemporary Islamic Economic Law - Dani Sintara; Abd Ulrahman Raad Nouri; Ahmad Rusly Purba; Sitta Saraya (MILRev: Metro Islamic Law Review, 2025)
This study examined the effectiveness of regional legislative oversight of fiscal policy following the revision of the Regional Finance Law, employing an analytical framework grounded in contemporary Islamic Economic Law. The research focuses on evaluating the extent to which the oversight function of the Regional House of Representatives (DPRD) contributes to promoting transparency, accountability, and justice in regional financial management. To this end, a qualitative-descriptive approach was employed, drawing on document analysis, in-depth interviews with legislative members and regional finance officials, as well as focus group discussions with experts in Islamic law and economics. The findings show that although the DPRD formally holds significant authority to monitor fiscal policy, the practical exercise of this oversight remains limited by weak institutional capacity and inconsistent integrity among actors. Political interests often dominate decision-making, fiscal literacy among legislators is uneven, and inter-institutional coordination is frequently inadequate. Nevertheless, the revised Regional Finance Law creates opportunities to strengthen budget transparency, improve accountability mechanisms, and broaden public participation in financial governance. From the perspective of contemporary Islamic Economic Law, fiscal oversight is not merely an administrative or technical duty but a moral trust (amānah) entrusted to leaders and representatives. Such oversight must therefore be directed toward realizing the higher objectives of public welfare (maṣlaḥah), fairness, and social justice. The study’s academic contribution lies in integrating juridical analysis of regional fiscal regulation with Islamic ethical principles, offering a normative-evaluative framework for advancing more equitable, participatory, and sustainable fiscal governance at the regional level.